Evaluating Ultrasonography Fetal Weight in Comparison to Actual Birth Weight in Term Pregnant Women at Tertiary Care Center Hospital - Fahad Ali, Maria Anum, Nighat Ali Shahi, Farah Khan, Muhammad Asad, Saqib Qamar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Prenatal mortality is very high in Pakistan. One of the most reasons is low birth weight and preterm babies. Hence, estimating the baby’s weight is paramount in antennal care. Birth weight refers to the body weight of a newborn. Multiple elements, like genetics epigenetics, nutritional and environmental factors can influence fetal weight. Ultrasonography is an important non-invasive tool for fetal weight estimation in normal and high-risk pregnancies. The role of ultrasound as a safe and non-invasive measurement for fetal growth and weight in pregnancy is well established. Objective: To determine the relationship between Sonographic fetal weight estimation in the prenatal period and definite birth weight in pregnant women in a multidisciplinary hospital set up Study design: A comparative study Place and Duration: Study was conducted in Department of Radiology, Chiniot General Hospital Korangi Karachi from January 2022 to June 2022 for six months duration. Methodology: The sample size is 50. Expecting mothers were taken in this study. These women were booked and they underwent an ultrasound examination of fetal weight in a prenatal period which was then correlated to actual fetal weight after birth by a pediatrician. Fetal weight was estimated and noted. It was measured by using. Hadlock’s formula: log (10) birth weight = 1.335-0.0034(abdominal circumference) (femur length) + 0.0316 (Biparietal diameter) +0.0457(abdominal circumference) +0.1623(femur length). Results: Most of our patients were between 20-30 year age brackets. There was a strong linear relationship between ultrasound fetal weight and real birth weight. The mean age of females was 26.12±5.65 years, and the mean BMI of patients was 26.17±4.19kg/m2. A strong positive correlation (r=0.575, p<0.05) was found between the fetal weight estimation on USG and actual birth weight. Conclusion: This study shows that ultrasound can be a valuable method of assessing fetal weight in pregnant women. Hence ultrasound can be used for informed decision-making for birthing decisions in expecting mothers. Keywords: Correlation, Ultrasonography, Birth Weight, Fetal